The optimal ratio of apparent digestible valine to lysine to maximize growth performance of the nursery pig - James, B.W.; Woodworth, J.C.; Goodband, Robert D.; Tokach, Michael D.; Nelssen, Jim L.; DeRouchey, Joel M.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
A total of 210 nursery pigs (initially 19.6 lb and approximately 28 d of age) were used in a 21-d growth assay to determine the optimal ratio of valine to lysine to maximize growth performance. The seven treatments consisted of a basal diet (14.2% CP; 1.07% apparent digestible lysine) with increasing ratios of valine:lysine (48, 53, 58, 63, 69, and 74%) and a negative control containing 0.97% lysine and 0.79% apparent digestible valine. Results indicate that the optimal apparent digestible valine:lysine ratio for the nursery pig is 58 and 64% for ADG and F/G, respectively. Therefore, most typical nursery diets will contain adequate amounts of valine to maximize growth performance of nursery pigs.
Keywords: Swine; Valine; Lysine; Nursery Pig